Detection of non-joint areas tiny strain and anti-interference voice recognition by micro-cracked metal thin film. (April 2017) - Wang, Chunfeng; Zhao, Jing; Ma, Chuang; Sun, Junlu; Tian, Li; Li, Xiaoyi; Li, Fangtao; Han, Xun; Liu, Chuntai; Shen, Changyu; Dong, Lin; Yang, Jin; et al.
Abstract: The poor detecting limit and attenuated sensitivity to tiny strain of a strain sensor retard their development toward practical applications ranging from wearable electronics, human healthcare monitoring to smart sensing system. Here, a strain sensor with high sensitivity to tiny strain, high flexibility, fast response and good stability is developed utilizing the micro-cracked metal thin film based on a novel working principle of combining the overlap mode with tunnel effect of the adjacent cracks. Monitoring of human motions and physiological signals as well as anti-interference voice recognition based on the sensor is demonstrated, showing its potential applications in wearable electronics, human healthcare monitoring and smart sensing system. Graphical abstract: Large-scale strain sensor with attributes of high sensitivity, highly flexibility, fast response and good stability is developed utilizing the micro-cracked metal thin film to satisfy practical applications in detection of human non-joint areas tiny strain and non-interference voice recognition, representing an important step toward design and applications of the strain sensor. Highlights: A lightweight, cost-effective and scalable strain sensor with excellent performance is developed by utilizing the micro-cracked metal thin film by combining the overlap modal with tunnel effect of the adjacent cracks; Detection of tiny strain of human non-joints, physiological pulse wave, canthus motion and any biological associated skin deformation is demonstrated; Mapping of strain distribution and anti-interference voice recognition system using this sensor pave the way to practical applications in smart sensor system and wearable electronics.